2005
DOI: 10.2166/wst.2005.0514
|View full text |Cite
|
Sign up to set email alerts
|

Combined biological and physico-chemical treatment of baker's yeast wastewater

Abstract: The UASB reactor (35 degrees C) was quite efficient for removal of bulk COD (52-74%) from the raw and diluted cultivation medium from the first separation process of baker's yeasts (the average organic loading rates varied in the range 3.7-16 g COD/I/d). The aerobic-anoxic biofilter (19-23 degrees C) can be used for removal of remaining BOD and ammonia from anaerobic effluents; however, it had insufficient COD to fulfil the denitrification requirements. To balance COD/N ratio, some bypass of raw wastewater (ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…However, the effluents of the anaerobic treatment stages should be further treated by the other treatment technologies in order to fulfill the discharge requirements for baker's yeast industries. Kalyuzhnyi et al (2005) studied the anaerobic treatment of baker's yeast industry effluent by an UASB reactor as a pre-treatment followed by aerobic-anoxic biofilter and coagulation processes. According to the results, the UASB reactor was found to be quite efficient for both raw and diluted samples with COD removal efficiencies between 52-74% for the OLRs of 3,7-16 g COD/L.day.…”
Section: Anaerobic Treatment Applications For the Treatment Of Baker'mentioning
confidence: 99%
“…However, the effluents of the anaerobic treatment stages should be further treated by the other treatment technologies in order to fulfill the discharge requirements for baker's yeast industries. Kalyuzhnyi et al (2005) studied the anaerobic treatment of baker's yeast industry effluent by an UASB reactor as a pre-treatment followed by aerobic-anoxic biofilter and coagulation processes. According to the results, the UASB reactor was found to be quite efficient for both raw and diluted samples with COD removal efficiencies between 52-74% for the OLRs of 3,7-16 g COD/L.day.…”
Section: Anaerobic Treatment Applications For the Treatment Of Baker'mentioning
confidence: 99%
“…Moreover, coagulation removal of COD and color from yeast wastewater using aluminum sulfate was investigated by Zhou et al Experimental results in this study indicated that the removal efficiency of COD and color were 67% and 89%, respectively. Thereupon, the contaminant removal by stand-alone processes is not sufficient and in order to achieve a high degree of purification, using combination method is necessary [36].In our previous work, we used hollow fiber membrane and filamentous fungus in MBR of baker's yeast wastewater treatment. COD and BOD5 of the wastewater were reduced to 488 and 70 mg/L, respectively, over a period of 45 days, while the turbidity of the wastewater reduced from 134-282 NTU to less than 2.5 NTU in the permeate stream [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Kalyuzhni ve diğ. [4] [16]. Vinasın diğer olası kullanım alternatifi de, içerdiği yüksek tuzluluğu dikkate almak kaydıyla, arazide gübre olarak kullanımdır [17,18].…”
Section: Introductionunclassified